The awareness of sustainable construction in Malaysia / Amirul Hafiz Jalil - Jalil, Amirul Hafiz (Faculty of Architecture, Planning and Surveying, 2015)
The aim of this research is to conduct research to see whether there is any knowledge or awareness from the construction workers and developers concerning the sustainable construction concept and to study whether there is any implementation of the application of sustainable construction in their building development or on the construction site. Due to lack of principles and knowledge on sustainable construction among the professionals that involved in the construction industry, the problem of unawareness is big. Based on the survey findings, most of construction workers are not aware about the sustainable way of construction whether it is from the aspect of economic or social. In order to ensure there is sustainable building development, awareness and the importance of this practice must be given out to the workers and developers. It can also be spread to the public and can be integrated with another economic and social programmes, education and health care.